Alterations of gut microbiota and metabolome with Parkinson's disease. (November 2021) - Yan, Zhenzhen; Yang, Fan; Cao, Jingwei; Ding, Wencai; Yan, Shi; Shi, Wanying; Wen, Shirong; Yao, Lifen
Abstract: Gut microbiota and amino acids that are one of their metabolites play important roles in the mechanism of pathology of Parkinson's disease (PD). It has been reported that the level of amino acids in vivo participate in neurodegeneration by regulating adaptive immune response, while the current researches on alteration of amino acids in gut microbiota are still insufficient. We hypothesized that alterations in gut microbiota might be accompanied by altered concentrations of amino acids, leading to the occurrence of PD. In this study, we collected stool samples from PD and healthy controls to analyse fecal microbiome and targeted metabolome by 16S ribosomal RNA (16S rRNA) gene sequencing and gas chromatography coupled to mass spectrometry (GC-MS). At the genus level, there was a greater abundance of Alistipes, Rikenellaceae_RC9_gut_group, Bifidobacterium, Parabacteroides, while Faecalibacterium was decreased in fecal samples from PD patients. Moreover, fecal branched chain amino acids (BCAAs) and aromatic amino acids concentrations were significantly reduced in PD patients compared to controls. Our study not only finds the abundance of certain gut microbiota in PD, but also reveals that it is related to BCAAs and aromatic amino acids. These findings are beneficial to identifying new therapeutic targets for PD by regulating diet and/or gut microbiota. Highlights: Gut microbial communities from patients with PD and controls were found to differ significantly. BCAAs and aromatic amino acids in PD patients were significantly decreased. The dysfunction of amino acid metabolism was related with the altered gut microbiota.